Jihad Ekonomi Dalam Perspektif Hadis: Tinjauan Terhadap Gerakan Boikot Produk Israel Sebagai Dukungan Terhadap Palestina - Idris Siregar; Dinar Maliki; Fakhrurrozi Nasution (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The conflict and occupation that have occurred in Palestine by Israel have been ongoing for over six decades, with oppression, destruction of buildings, and civilian deaths occurring far too frequently. This long-standing conflict and occupation has garnered global attention, as it is highly sensitive due to its direct association with religion. The prolonged conflict has also devastated the Palestinian economy, necessitating donation assistance. The struggle or jihad in support of Palestine from various parts of the world has emerged as a force, with global condemnation of Israel's occupation through boycotts of Israeli products and those supporting Israel. Through qualitative research in the form of literature studies, researchers aim to explore the hadith's perspective on boycotting colonial products. The findings of this research indicate that boycotting products that aid colonization is justified, as it is forbidden to purchase goods used to combat Muslims and strengthen the position of colonizers. This research is expected to provide a foundation for thought and action in engaging in boycotts as a form of solidarity with Palestine.